Direct observation of electrostatic charging in 3D printing - Ezequiel Lorenzett; Yan A. S. da Campo; Milton A. F. Neto; Thiago A. L. Burgo (Nature Communications)
Abstract The spontaneous electrification of surfaces and interfaces is a widespread phenomenon that produces unexpected effects in chemical reactivity and mass charge transfer, revealed in abundant literature over the past twenty years. The pervasive presence of electrostatic charges originates from many sources, including friction, mechanochemical reactions, phase change, flexoelectricity, and others. Since fused deposition modeling undergoes most well-known electrification mechanisms, it would be not surprising that 3D-printed objects display large amounts of charge. Here we uncover the hitherto unexplored realm of electrostatic charging in 3D printing, underscores the impact of printing parameters on charge generation in polymers. Substrates, printing speed, temperature, and printing direction each exert distinct impacts on charge buildup, depending upon the material used for printing. We also develop simple protocols employing common multimeters for charge monitoring, while substrates subjected to corona charging or triboelectrification demonstrate effective methods for charge control or mitigation. An original development is achieved by demonstrating the ability to print quasi-electrets, indicating a potential revolution in electret technology. The implications of these findings establish the groundwork for advancements in 3D printing technology and electrostatics, creating new scientific opportunities for a better understanding of matter.